Outpatient Pharmacotherapy for Neonatal Abstinence Syndrome - Maalouf, Faouzi I. (J Pediatr, 2018)
OBJECTIVE: To determine differences in lengths of stay, length of therapy, emergency department (ED) utilization, and hospital readmissions between infants with neonatal abstinence syndrome (NAS) treated exclusively with in-patient pharmacotherapy compared with those discharged on outpatient pharmacotherapy. STUDY DESIGN: This retrospective cohort study of infants enrolled in the Tennessee Medicaid program used administrative and vital records data from 2009 to 2011. Medical record review was used to confirm cases of NAS and classify treatment type. Negative binomial regression was used to compare length of therapy and ordinal regression was used to determine frequency of ED visits and hospital readmissions. RESULTS: Among a cohort of 736 patients with confirmed NAS, 72.3% were treated with pharmacotherapy of which approximately one-half (45.5%) were discharged home on outpatient medications. For infants discharged on out-patient pharmacotherapy, initial hospital length of stay was shorter (11 vs 23 days; P < .001) and length of therapy was longer (60 vs 19 days; adjusted incidence rate ratio [aIRR] 2.84, 95%CI 2.31–3.52). After adjusting for potential confounders, infants discharged on outpatient pharmacotherapy had a greater number of ED visits within 6 months of discharge (adjusted odds ratio [aOR] 1.52, 95% CI 1.06–2.17) compared with those treated as inpatients alone. CONCLUSIONS: Outpatient pharmacotherapy for NAS was associated with higher length of therapy and higher rates of ED utilization when compared with infants treated exclusively as inpatients. Future research should focus on improving the efficiency of NAS management while minimizing postdischarge complications.